BENTUK TINDAK PIDANA KORUPSI DI SEKTOR BARANG DAN JASA DALAM PERSPEKTIF HUKUM EKONOMI - Sri Agustini (Ensiklopedia Social Review, 2019)
Procurement of goods and services is not only limited to the selection of project partners with the purchasing department or the official two-party agreement, but covers the entire process from the start of planning, preparation, licensing, determination of tender winners to the implementation and administrative processes in procurement of goods, work or services such as technical consulting services, financial consulting services, legal consulting services or other services. Article 33 Paragraph (4) of the 1945 Constitution states: "The national economy is organized based on economic democracy with the principle of togetherness, efficiency, justice, sustainability, environmental insight, independence, and by maintaining a balance of national progress and unity." It is clear in Article 33 of the 1945 Constitution that economic democracy is thought, where democracy has a characteristic that the manifestation process is realized by all members of the community for the benefit of the whole community, and must serve the welfare of all people. To prevent corruption in the service sector, the Presidential Regulation Number 4 of 2015 concerning the Fourth Amendment to Presidential Regulation Number 54 of 2010 concerning Procurement of Government Goods / Services was issued. The Perpres should be carried out in accordance and in line with the mandate of Article 33 of the 1945 Constitution. The principles of PBJP are governed based on the principles of economic democracy, in order to realize national independence, improve the country's financial efficiency, maintain the balance and unity of the national economy. Keywords: Corruption Crime, Goods and Services, Economic Law